(23) Keadilan Sosial dalam Administrasi Publik: Membangun Masyarakat yang Adil dan Inklusif - Ditasman, Ditasman; Dwisnu, Erlian; Susanto, Akbar Ari; Alvego, Redho (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
Social justice in public administration is a key cornerstone in efforts to build a just and inclusive society. Social justice-oriented public administration aims to eliminate inequality, distribute resources equitably, and provide fair public services to all citizens. In this context, public administration becomes an important tool in realizing the vision of a society based on the principles of justice, equality and inclusion, so that every individual has equal opportunities to develop and participate in social and economic life. Thus, it is important for the government and stakeholders to remain committed to promoting social justice in every aspect of public administration in order to create a more just and inclusive society.